The Application Of Story Methods With Islamic Nuances In Realizing Akhlakul Karimah For Students Of Sunggal Islamic Aliyah Madrasah - Ababil, Panji (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
This study aims to realize akhlakul karimah in students of Sunggal Aliyah Islamic Madrasah using the application of the Islamic nuanced story method to the subject of Aqidah Akhlak. This study used field research with a qualitative descriptive approach. namely direct survey researchers to the field. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis in this study used data collection analysis, data presentation and conclusion. Based on the results of the research and data analysis, it can be concluded that the application of the story method with Islamic nuances in the subject of natural moral principles to realize akhlakul karimah in MA Islamiyah Sunggal is: the concept of applying the story method with Islamic nuances in the subject of aqidah morals is an appropriate and interesting method and becomes an alternative learning for students. Students get good grades in the subject of aqidah morals and increase to 80-90 as well as an increase in better personality and discipline experiencing development in a much better direction.Keywords: Islamic Stories, Akhlakul karimah, moral beliefs